Petrology, geochemistry and magnetic properties of Sadara sill: Evidence of rift related magmatism from Kutch basin, northwest India - Ray, Arijit; Patil, S.K.; Paul, D.K.; Biswas, S.K.; Das, Brindaban; Pant, N.C. (My University, 2006)
Mafic volcanic rocks of the Mesozoic Kutch basin represent the earliest phase of Deccan volcanic activity. An olivine-clinopyroxene-plagioclase-phyric undersaturated basalt occurs as a sill near Sadara in the Pachham upland, Northern Kutch. The Sadara sill is deformed and emplaced along faults. The sill is alkaline in character and is transitional between basalt and basanite. Compared to primitive mantle, the Sadara sill is enriched in Sr, Ba, Pb and LREE but depleted in Nb, Cr, Y, Cs and Lu. Fractional crystallization of olivine and clinopyroxene from an alkaline mafic melt generated by low degree partial melting of mantle peridotite can explain the observed chemical variation in the sill.IRM and L-F test experiments and mineral analyses show titano-magnetite as the major remanence carrying magnetic mineral. AF and thermal demagnetizations of the Sadara sill yielded a mean ChRM direction as D=315.6°, I=−43.0° (α95=9.78; k=25.38) and the corresponding VGP at 25°S; 114.6°E (dp/dm=6.58°/11.6°). The Sadara sill pole is significantly different from those of the Deccan (65Ma) and the Rajmahal Traps (118Ma) but is close to the Cretaceous poles of 85–91Ma rock units from southern India. This suggests a pre-Deccan age for the sill.
Keywords: Deccan traps; Flood basalts; Paleomagnetism; Deccan volcanism; Geochemistry; Kutch basin; Mafic volcanic rocks; Petrogenesis; kutch (India)